A Consensus-Based Educational Approach for Large Lecture Classes. Issue 1 (2nd January 2022) - Allen, Andrew P.; Shinohara, Russell T.; Kroetz, Mary B.
Abstract: Peer learning is an active learning technique that has been used for students to internalize difficult concepts. We have developed a method of peer learning, a consensus-based education approach, which allows for discussion and class consensus in large lecture classes. We tracked student success on concepts that employed the consensus-based education approach and found that students significantly improved on their mastery of a majority of these concepts. Students who mastered these concepts also performed better overall throughout the class. Finally, this consensus-based educational approach can easily be adapted to remote synchronous learning platforms which have been necessitated by the SARS-CoV-2 pandemic.